Fetal macrosomia and its associated factors among pregnant women delivered at national referral hospital in Uganda, a case-control study. - Peter Wanyera; Eve Nakabembe; Mike Nantamu Kagawa (PLoS ONE)
Background The delivery of macrosomic newborns (newborns>4000gm) is increasing steadily worldwide and yet it is associated with many complications. The risk factors for fetal macrosomia include weight at first antenatal visit, previous delivery of a large newborn, newly diagnosed diabetes in pregnancy, increasing number of deliveries, a male fetus, and many others. There is paucity of data on fetal macrosomia in Uganda and the objective of this study therefore was to determine the risk factors for fetal macrosomia among women who delivered at a National Referral Hospital in Kampala, Uganda.. Methods An unmatched case-control study was conducted among 177 cases and 354 controls at Kawempe National Referral Hospital. Data was collected using interviewer-administered questionnaires for three months from 8th February 2021-25th May 2021. Comparison between the cases and the controls was done using the student t-test for normally distributed continuous data. The Mann Whitney U Test (Wilcoxon Rank Sum Test) was used to compare data that was not normally distributed. Binary logistic regression was used in bivariate and multivariate analysis for factors associated with fetal macrosomia using STATA version 16.0. Results A total of 531 participants were recruited into the study in a ratio of one case to two controls. The mean age for cases was 28.5 ± 5.9 years and 25.9 ± 5.4 years for controls while the mean weight was 78.4 ± 12.4Kgs for cases and 68.2 ± 11.7 Kg for controls. Risk factors for fetal macrosomia included maternal age ≥40 years (aOR = 7.4, [95%CI 1.37-39.44], p value = 0.020), maternal weight ≥80 kg (aOR = 4.0, [95%CI 2.15-7.40], p value <0.001), maternal height ≥160 cm (aOR = 1.6, [95%CI 1.02-2.51], p value = 0.040), being married (aOR = 2.55, [95%CI 1.08-6.06], P value = 0.038), gestation age ≥40 weeks (aOR = 1.8,[95%CI 1.16-2.82], p value = 0.009), previous macrosomia (aOR = 2.2, [95%CI 1.26-3.81], p value = 0.006) and male babies (aOR = 1.78, [95%CI 1.14-2.77], p value = 0.011). Conclusions The main risk factors for fetal macrosomia were higher maternal weight and height, advanced age as well as post-datism, previous delivery of a large newborn, male fetus and being in a marital relationship. A well-designed protocol to identify women with risk factors for fetal macrosomia may help to provided targeted interventions in this group.